Waveguide dispersion in a lightguide of compressed ellipse-shaped cross-section - Singh V.; Prasad B.; Ojha S.P. (My University, 2025)
This paper describes the theoretical analysis for the temporal broadening of a pulse arising due to dispersion in an optical waveguide with a cross-sectional shape resembling an ellipse compressed along the minor axis (ECMI). Denoting the normalized frequency parameter as V, and the normalized propagation constant as b the explicit expression for d(Vb)/dV have been derived. For this we use the appropriate coordinate systems and the boundary conditions of the proposed waveguide under the weak guidance condition. The variation of d(Vb)/dV with V has also been obtained. It is seen that the curves are of the expected shapes. Moreover, the computed values of d(Vb)/dV for the ECMI are greater than those for the step index fiber. The group delay is only slightly altered by the distortion of the circular shape to the compressed ellipse shape.